2016
DOI: 10.1111/ejn.13444
|View full text |Cite
|
Sign up to set email alerts
|

Early life diets with prebiotics and bioactive milk fractions attenuate the impact of stress on learned helplessness behaviours and alter gene expression within neural circuits important for stress resistance

Abstract: Manipulating gut microbes may improve mental health. Prebiotics are indigestible compounds that increase the growth and activity of health-promoting microorganisms, yet few studies have examined how prebiotics affect CNS function. Using an acute inescapable stressor known to produce learned helplessness behaviours such as failure to escape and exaggerated fear, we tested whether early life supplementation of a blend of two prebiotics, galactooligosaccharide (GOS) and polydextrose (PDX), and the glycoprotein la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 75 publications
2
64
1
Order By: Relevance
“…We chose to start them at such an early age because it has been demonstrated that the gut bacteria can be more easily shaped by exogenous factors such as exercise and a prebiotic diet very early in life, which leads to what is thought to be a stress-protective gut bacteria pheontype (Mika et al, 2015b; Mika and Fleshner, 2016). Additionally, starting the prebiotic diet as early as PND 24 has been shown to alleviate the negative consequences of stress in adulthood (Mika et al, 2016). All of these effects were demonstrated in the F344 rat strain.…”
Section: Methodsmentioning
confidence: 99%
“…We chose to start them at such an early age because it has been demonstrated that the gut bacteria can be more easily shaped by exogenous factors such as exercise and a prebiotic diet very early in life, which leads to what is thought to be a stress-protective gut bacteria pheontype (Mika et al, 2015b; Mika and Fleshner, 2016). Additionally, starting the prebiotic diet as early as PND 24 has been shown to alleviate the negative consequences of stress in adulthood (Mika et al, 2016). All of these effects were demonstrated in the F344 rat strain.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, this definition has been updated to include non‐carbohydrate substances, applications to body sites other than the gastrointestinal tract and diverse categories other than food (Gibson et al., ). Recently, we (Burokas et al., ; McVey Neufeld et al., ) and others (Mika et al., ; Tarr et al., ; Thompson et al., ; Williams et al., ) have shown that prebiotics can have a positive effect on physiology and behaviour and can reverse the effects of stress and immune activation in adult animals. Moreover, research now shows that a combination of prebiotics and MFGM improves sleep and attenuates the impact of stress in rats (Mika et al., ; Thompson et al., ); however, the ability of MFGM to counter the enduring effects of early‐life stress remains unexplored.…”
Section: Introductionmentioning
confidence: 91%
“…maternal separation, neurodevelopment, postnatal, visceral hypersensitivity the effects of stress and immune activation in adult animals. Moreover, research now shows that a combination of prebiotics and MFGM improves sleep and attenuates the impact of stress in rats (Mika et al, 2017;Thompson et al, 2016); however, the ability of MFGM to counter the enduring effects of early-life stress remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[89] GF animals also exhibit increased depressive-like behavior. [90] Additional preclinical studies have shown that anxiety-and/or depression-like behaviors are also altered by certain probiotic treatments, [62] prebiotics, [91][92][93] and antibiotics. [94] In humans, alterations in the microbiota have been observed across a variety of amygdala-related clinical disorders, including depression.…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…[90,96] Finally, different probiotic strains have been shown to reduce symptoms of anxiety and depression across several studies in clinical and healthy populations. [97,98] While there have also [5,9,10,88,90] Anxiolytic effects, sometimes sex-specific, in mice (light-dark box, elevated-plus maze) [72,113] Anxiolytic effects in mice (open field, defensive marble burying, elevated-plus maze, light-dark box) [91,93] Strain-specific anxiolytic effects in humans (e.g., Beck Anxiety Index, Hospital Anxiety & Depression Scale) and rodents (defensive marble burying, elevated-plus maze, open field) [11,62,133,134] Transplant from humans with depression or comorbid IBS and anxiety increases anxietylike behavior in mice (open field, step-down test, light-dark box) [96,125] Heightened anxiety in rats (open field) [89] Depression Increased depressive-like behavior in mice (forced swim) [90] Increased depressive-like behavior in rats (forced swim) [94] Antidepressant effects in mice and rats (forced swim, tail suspension, learned helplessness after inescapable shock) [91,92] Strain-specific antidepressant effects in humans (e.g. Beck Depression Inventory, Hospital Anxiety & Depression Scale) and rodents (tail suspension test, forced swim, sucrose preference) [11,97,98,133,134] Transplant from depressed human donors induces depressive-like behavior in mice (sucrose preference, forced swim [varied results], tail suspension test) [90,96] Learned fear Impaired fear recall in adult mice [101] Acute administration enhances fear extinction in rodents and exposure therapy in humans, [103,104] reduces fear recall in huma...…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%